Ten years of global burned area products from spaceborne remote sensing—A review: Analysis of user needs and recommendations for future developments - Mouillot, Florent; Schultz, Martin G.; Yue, Chao; Cadule, Patricia; Tansey, Kevin; Ciais, Philippe; Chuvieco, Emilio (International journal of applied earth observation and geoinformation, 2014)
Early global estimates of carbon emissions from biomass burning were based on empirical assumptions of fire return interval in different biomes in the 1980s. Since then, significant improvements of spaceborne remote sensing sensors have resulted in an increasing number of derived products characterizing the detection of active fire or the subsequent burned area (GFED, MODIS MCD45A1, L3JRC, Globcarbon, GBS, GLOBSCAR, GBA2000). When coupled with global land cover and vegetation models allowing for spatially explicit fuel biomass estimates, the use of these products helps to yield important information about the spatial and the temporal variability of emission estimates. The availability of multi-year products (>10 years) leads to a better understanding of uncertainties in addition to increasing accuracy. We surveyed a wide range of users of global fire data products whilst also undertaking a review of the latest scientific literature. Two user groups were identified, the first being global climate and vegetation modellers and the second being regional land managers. Based on this review, we present here the current needs covering the range of end-users. We identified the increasing use of BA products since the year 2000 with an increasing use of MODIS as a reference dataset. Scientific topics using these BA products have increased in diversity and area of application, from global fire emissions (for which BA products were initially developed) to regional studies with increasing use for ecosystem management planning. There is a significant need from the atmospheric science community for low spatial resolution (gridded, 1/2 degree cell) and long time series data characterized with supplementary information concerning the accuracy in timing of the fire and reductions of omission/commission errors. There is also a strong need for precisely characterizing the perimeter and contour of the fire scar for better assimilation with land cover maps and fire intensity. Computer and earth observation facilities remain a significant gap between ideal accuracies and the realistic ones, which must be fully quantified and comprehensive for an actual use in global fire emissions or regional land management studies.